Strategies for dealing with sin in relation to poverty - Kakwata, Frederick N (Stellenbosch Theological Journal, 2016)
This article attempts to analyse and evaluate strategies for overcoming sin in relation to poverty in the African context. However, to address sin in this context means eliminating the very causes that give rise to the social malady. It is argued that the classical strategies (regeneration, reform and revolution) used thus far to address the issue of social sin, seem unable to deal with all its causes. This article proposes an alternative strategy based on the three offices of Christ, namely prophetic, priestly and royal, for a relevant approach to the issue of sin in poverty-related contexts within an African environment.